A proactive Medium Access Control (MAC) for finite-sized machine-to-machine (M2M) communication networks. (September 2022) - Fazil, Adnan; Hasan, Aamir; Alyaei, Bahman R.; Khan, Khurram; Zakwan, Muhammad
Abstract: In order to establish communication links among different communication devices or machines, the Medium Access Control (MAC) has to schedule the simultaneous transmissions by the contending nodes to constrain the probability of outage at each receiver. An efficient channel access scheme should be able to schedule the highest number of concurrent transmissions while being easy to implement with minimal coordination between the contending nodes. The existing MAC schemes provide network-wide solutions without adaptiveness, such as in existing guard zone-based solutions. On the other hand, an adaptive channel access scheme is proposed in this paper, which instead of declaring a network-wide fixed guard zone employs each interferer's Transmitter–Receiver (Tx–Rx) separation to conclude its incorporation in the scheduled transmissions. The suggested scheme warrants the spatial separation among the scheduled links by suppressing the dominant interferers. The proposed MAC design functions approximately as good as the centralized, otherwise infeasible, joint scheduling and power control algorithm. In addition, the recommended scheme has proved its strength by outperforming both Carrier Sense Multiple Access (CSMA) and fix-sized guard zone schemes by significant margins under strict outage constraints and high contention density. The proposed scheme provided up to 100% and 60% better transmission capacity when compared with CSMA and fix-sized guard zone-based scheme, respectively. This paper also presents the closed-form results for the optimal guard zone size multiplier and the corresponding throughput capacity in terms of various network variables, such as contention density, outage constraint, Tx–Rx separation, network's path loss exponent and spreading factor.